Nanosonosensitizer-Augmented Sonodynamic Therapy Combined with Checkpoint Blockade for Cancer Immunotherapy - Lin X (Dove Medical Press, 2021)
Xiaoning Lin,1,* Rong Huang,2,* Yanlin Huang,1,* Kai Wang,3 Heng Li,1 Yiheng Bao,1 Chaohui Wu,4 Yi Zhang,5 Xinhua Tian,1 Xiaomin Wang6 1Department of Neurosurgery, Zhongshan Hospital Xiamen University, Xiamen, 361004, People’s Republic of China; 2Department of Child Health, Women and Children’s Hospital, Xiamen University, Xiamen, 361003, People’s Republic of China; 3School of Public Health, Xiamen University, Xiamen, 361102, People’s Republic of China; 4Department of Thoracic Surgery, Zhongshan Hospital Xiamen University, Xiamen, 361004, People’s Republic of China; 5Department of Breast Surgery, Xiamen TCM Hospital, Xiamen, 361001, People’s Republic of China; 6Fujian Provincial Key Laboratory of Chronic Liver Disease and Hepatocellular Carcinoma, Zhongshan Hospital Xiamen University, Xiamen, 361004, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaomin WangFujian Provincial Key Laboratory of Chronic Liver Disease and Hepatocellular Carcinoma, Xiamen University Affiliated Zhongshan Hospital, Xiamen, 361004, People’s Republic of ChinaEmail wxm2203@xmu.edu.cnXinhua TianDepartment of Neurosurgery, Zhongshan Hospital Xiamen University, Xiamen, 361004, People’s Republic of ChinaEmail txhmd@163.comIntroduction: Sonodynamic therapy (SDT) has good targeting and non-invasive advantages in the treatment of solid cancers, and checkpoint blockade immunotherapy is also a promising treatment to cure cancer. However, their antitumor effects are not sufficient due to some inherent factors. Some studies that combined SDT with immunotherapy or nanoparticles have managed to enhance its efficiency to treat cancers.Methods: In this work, an effective therapeutic strategy that can potentiate the antitumor efficacy of anti-PD-L1 antibody (aPD-L1) is developed by the use of cascade immuno-sonodynamic therapy (immuno-SDT). Titanium dioxide (TiO2), a nanostructured agent for SDT, sonosensitizer Chlorin e6 (Ce6), and immunological adjuvant CpG oligonucleotide (CpG ODN), are used to construct a multifunctional nanosonosensitizer (TiO2-Ce6-CpG). Then, we conducted in vitro and in vivo experiments to explore the antitumor effect of TiO2-Ce6-CpG under ultrasound (US) treatment.Results: The characterization tests showed that the nanosonosensitizers are polycrystalline structure with homogeneous sizes, resulting in a good drug loading efficiency. The innovative nanosonosensitizers (TiO2-Ce6-CpG) can not only effectively inhibit tumor growth but also stimulate the immune system to activate the adaptive immune responses, using the TiO2-Ce6 to augment SDT and the immune adjuvant CpG to enhance the immune response. After combined with the aPD-L1, the synergistic effect could not only efficiently inhibit the primary tumor growth but also lead to an inhibition of the non-irradiated pre-existing distant tumors by inducing a strong tumor-specific immune response.Conclusion: In this study, we present an effective strategy for tumor treatment by combining nanosonosensitizer-augmented SDT and aPD-L1 checkpoint blockade. This work provides a promising strategy and offers a new vision for treating malignant tumors.Keywords: cancer immunotherapy, sonodynamic therapy, titanium dioxide nanoparticles, sonosensitizer, checkpoint blockade